PKC-ζ Aggravates Doxorubicin-Induced Cardiotoxicity by Inhibiting Wnt/β-Catenin Signaling - Cao, Yan-Jun; Li, Jing-Yan; Wang, Pan-Xia; Lin, Zhi-Rong; Yu, Wen-Jing; Zhang, Ji-Guo; Lu, Jing; Liu, Pei-Qing (Frontiers in Pharmacology, 2022)
Doxorubicin (Dox) is a chemotherapeutic drug used to treat a wide range of cancers, but its clinical application is limited due to its cardiotoxicity. Protein kinase C-ζ (PKC-ζ) is a serine/threonine kinase belonging to atypical protein kinase C (PKC) subfamily, and is activated by its phosphorylation. We and others have reported that PKC-ζ induced cardiac hypertrophy by activating inflammatory signaling pathway. This study focused on whether PKC-ζ played an important role in Dox-induced cardiotoxicity. We found that PKC-ζ phosphorylation was increased by Dox treatment in vivo and in vitro. PKC-ζ overexpression exacerbated Dox-induced cardiotoxicity. Conversely, knockdown of PKC-ζ by siRNA relieved Dox-induced cardiotoxicity. Similar results were observed when PKC-ζ enzyme activity was inhibited by its pseudosubstrate inhibitor, myristoylated. PKC-ζ interacted with β-catenin and inhibited Wnt/β-catenin signaling pathway. Activation of Wnt/β-catenin signaling by LiCl protected against Dox-induced cardiotoxicity. Wnt/β-catenin inhibitor XAV-939 aggravated Dox-caused decline of β-catenin and cardiomyocytes apoptosis and mitochondrial damage. Moreover, activation of Wnt/β-catenin suppressed aggravation of Dox-induced cardiotoxicity due to PKC-ζ overexpression. Taken together, our study revealed that inhibition of PKC-ζ activity was a potential cardioprotective approach to preventing Dox-induced cardiac injury.